The essential role of tumor suppressor gene ING4 in various human cancers and non-neoplastic disorders. Issue 1 (30th January 2019) - Du, Yang; Cheng, Yan; Su, Guanfang
Abstract : Inhibitor of growth 4 (ING4), a member of the ING family discovered in 2003, has been shown to act as a tumor suppressor and is frequently down-regulated in various human cancers. Numerous published in vivo and in vitro studies have shown that ING4 is responsible for important cancer hallmarks such as pathologic cell cycle arrest, apoptosis, autophagy, contact inhibition, and hypoxic adaptation, and also affects tumor angiogenesis, invasion, and metastasis. These characteristics are typically associated with regulation through chromatin acetylation by binding histone H3 trimethylated at lysine 4 (H3K4me3) and through transcriptional activity of transcription factor P53 and NF-κB. In addition, emerging evidence has indicated that abnormalities in ING4 expression and function play key roles in non-neoplastic disorders. Here, we provide an overview of ING4-modulated chromosome remodeling and transcriptional function, as well as the functional consequences of different genetic variants. We also present the current understanding concerning the role of ING4 in the development of neoplastic and non-neoplastic diseases. These studies offer inspiration for pursuing novel therapeutics for various cancers.